PEMBELAJARAN BERBASIS ETNOMATEMATIKA DENGAN MEMODELKAN MOTIF BATIK GAJAH MADA - umy zahroh (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2020)
Abstract This research was based on mathematics learning in schools that are too formal and theoretical, and are less varied so it affects students' interest in learning mathematics. For this reason, a connection between mathematics outside of school and school mathematics is needed. One way that can be used is to utilize the ethnomathematics approach as the beginning of formal mathematics teaching which is suitable with the students' level of development who are at a concrete operational stage. The same thing was stated that the presence of mathematics with cultural nuances would make a major contribution to school mathematics. The objectives of this research were (1) to find out mathematical activities in the form of numerating, measuring, and calculating in batik activities. (2) To find out the mathematical concepts of geometry and geometrical transformations contained in batik motifs. This research used ethnographic research with a qualitative approach. Data collection techniques used were observation, interviews, and documentation. Data analysis technique used data reduction, data presentation, drawing conclusions and verification. The results showed that (1) in the batik activity at the Gajah Mada Tulungagung batik production house there were mathematical activities in the form of counting when determining the number of tools and materials needed, measuring fabric, calculating night requirements, calculating color comparisons, calculating waterglass requirements, and when calculating water needs. Measuring activity is seen during the process of measuring fabrics and designing batik patterns. The next step of counting activity is seen during the process of cutting fabric from 60 yards into 27 pieces, calculating the plastisin required for 2 meter fabric, and when mixing several colors. (2) There is a mathematical concept of geometry in the form of points, curved lines, triangles and circles, and the concept of geometrical transformation in the form of translation Keywords: Ethnomatematics, Mathematics, Culture, Batik Abstrak Pembelajaran matematika di sekolah yang formal dan teoritis, serta kurang bervariasi akan mempengaruhi minat peserta didik dalam mempelajari matematika. Untuk itu diperlukan keterhubungan antara matematika di luar sekolah dengan matematika sekolah. Salah satu cara yang dapat digunakan adalah dengan memanfaatkan pendekatan ethnomathematika sebagai awal dari pengajaran matematika formal yang sesuai dengan tingkat perkembangan siswa yang berada pada tahapan operasional konkrit. Hal yang sama dikemukakan bahwa kehadiran matematika yang bernuansa budaya akan memberikan kontribusi yang besar terhadap matematika sekolah.  Penelitian ini bertujuan (1) untuk mengetahui aktivitas matematika berupa membilang, mengukur, dan menghitung pada aktivitas membatik. (2) Untuk mengetahui konsep matematika geometri dan transformasi geometri yang terdapat pada motif batik. Penelitian ini menggunakan jenis penelitian etnografi dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Dalam menganalisis data menggunakakan reduksi data, penyajian data, menarik kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa (1) dalam aktivitas membatik di rumah produksi batik Gajah Mada Tulungagung terdapat aktivitas matematika yaitu berupa membilang saat menentukan banyaknya alat dan bahan yang diperlukan, mengukur kain, menghitung kebutuhan malam, menghitung perbandingan warna, menghitung kebutuhan waterglass, dan saat menghitung kebutuhan air. Aktivitas mengukur terlihat saat proses mengukur kain dan mendesain pola batik. Selajutnya aktivitas menghitung terlihat saat proses pemotongan kain dari 60 yard menjadi 27 potong, menghitung kebutuhan malam untuk kain 2 meter, dan saat mencampur beberapa warna. (2) Terdapat konsep matematika geometri berupa titik, garis lengkung, segitiga, dan lingkaran, serta konsep transformasi geometri berupa translasi, rotasi, dan refleksi Kata Kunci: Etnomatematika, Matematika, Budaya, Batik